The Origins and Development of Athletics Among the Military, European and Migrant Communities in Nineteenth-Century Singapore, 1819–1899 - Lim, P.H.; Aman, M.S. (Taylor & Francis, 2014)
There is no detailed study about the origins of athletics in nineteenth-century Singapore. This research relied primarily on newspaper records, official census reports, club membership and school enrolment to study the origins and degree of participation in athletics in the military, European, Eurasian, Chinese, Malay and Indian communities. It also makes comparison to the diffusion and transmission of athletics within the global and the various local communities. The findings suggest that a ‘foot-race’ was first introduced primarily to the Malay and Chinese community in the annual New Year regatta since 1837. Athletic events were held by the troops at Tanglin Barracks and Fort Canning in 1877 following the practice and tradition of the military colleges and camps in England. The athletic meets were also organised by the European, Eurasian, Straits Chinese, Malay and Tamil sports clubs starting in 1880 thereafter. It was introduced to three English boys' schools since 1887 after the establishment of the Education Department in 1872 and the organisation of Government and aided English schools. There were no physical education or athletic programme in the English girls' schools and in the elementary Malay, Chinese and Anglo-Tamil schools.